KONTRAK ELEKTRONIK DALAM PERDAGANGAN INTERNASIONAL DITINJAU DARI PERSPEKTIF HUKUM POSITIF INDONESIA - Derry Angling Kesuma (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2018)
The growth of international trade and trade as a result of technological developments in the last ten to fifteen years, which is commonly referred to as "globalization" has changed the perception of governments and international business people by seeking harmonization between positive law and economics. This research is a qualitative research with a juridical-normative approach. The data in this study are secondary data collected through the literature study method. This study emphasizes the understanding of electronic contracts from a positive legal perspective in the context of international trade relations. From this research, it can be seen that the rules regarding electronic contracts regarding International Trade in Indonesia are still regulated in Law Number 11 of 2008 concerning ITE and Law Number 19 of 2001 concerning Amendments to Law Number 11 of 2011 concerning ITE.